MORPHO-STOMATA EFFECT OF SODIUM AZIDE ON TWO VARIETIES OF GROUNDNUT (Arachis hypogaea L.) (FUDMA JOURNAL OF SCIENCES, 2020)
Dry seeds of groundnut (Arachis hypogaea L.) varieties Samnut 23 and Samnut 24 were obtained from Kashere market and duly identified at the Ministry of Agriculture, Gombe State, Nigeria. The seed were treated with five (5) different sodium azide concentrations (0.01, 0.02, 0.03, 0.04 and 0.05 M) to evaluate the plant growth parameters and stomata cell size of the varieties in response to treatment. Data obtained were subjected to Analysis of variance using Statistical Package for the Social Sciences SPSS, version 23 and the means were separated using Duncan Multiple Range Test (DMRT) at 0.05 probability level. The plant vegetative traits evaluated showed significance responses to different treatment concentrations. The highest vegetative growth (Plant height, number of leaves, and number of branches) was induced by 0.01M concentration at 10 week after sowing (WAS). Generally, the performances of the two varieties were optimal in response to 0.01M concentration and both varieties (Samnut 23 and Samnut 24) responded differently to sodium azide treatment of different concentrations. In both varieties, the anatomical feature (stomatal size) is significantly influenced by the sodium azide. These findings suggest that sodium azide can be utilized to create variability among existing germplasm for improving morphological and anatomical trait of groundnut.
Keywords: Arachis hypogaea, sodium azide, morpho – stomata effect.